Analysis of the Socio-economic Contributions of Palo Verde national park “A nest for Research and Education” 2009 - Moreno Díaz, Mary Luz (2010)
The Project „‟Systematization and Analysis of the Contributions of National Parks and Biological Reserves to the Economic and Social Development in Costa Rica, Benin and Bhutan’’ was developed by CINPE and executed under the Program of South-South Cooperation (financed by the Kingdom of the Netherlands and administrated by Fundecooperación), from which this case study is integral part. This project was developed in three countries and it was led by the International Centre for Policy for Sustainable Development (CINPE) of the Universidad Nacional (UNA) of Costa Rica. The counterpart in Benin is the Centre Béninois pour l'Environnement et le Développement Economique et Social (CEBEDES). While in Bhutan is the Division of Nature Conservation of the Ministry of Agriculture and Forests of the Royal Government of Bhutan. The project's general objective is to systematize and analyze the socio-economic contribution – decentralized and centralized - "of national parks and biological reserves to the economic and social development of Costa Rica, Bhutan and Benin and make policy recommendations of management to support policy makers in the management of national parks and biological reserves. Palo Verde National Park (PNPV), declared wetland of international significance in 1991 (ramsar site), it is one of the three case studies analyzed in Costa Rica. This one was selected by a group of experts to accomplish several criteria, which place it as a Protected Wildlife Area, important for the protection of unique ecosystems and diversity of landscapes. This PN is also distinguished by research and education generated on it. A great number of scientists, academicians, and students come to Costa Rica in order to visit the park. The methodology used in the study combines the cluster analysis with a dynamics of added value chain, where PNPV constitutes the material basis that underpins the existence and reproduction of diverse socio-economic activities that depend directly and indirectly on their preservation. These activities report qualitative and quantitative contributions to various social actors at local, regional, national and international levels. In an effort to become these contributions in monetary terms, the search, systematization and analysis of primary and secondary information allows an approximate estimation of the contributions of PNRV for 2009. In this regard, the global contribution of this area amounts approximately to ¢1.106.217.230 (US$1.936.446.4). From this total, around 29,53% remains at local level, 1,58% at regional level, 61,41% at national level and 7, 48% at international level.